Formulation of Islamic Education in Digital Society - Kusnawan; Alijaya, Adudin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This article discusses the formulation of Islamic education in the context of an evolving digital society. The main focus is on how Islamic values and principles can be integrated with modern technology to create a relevant and effective education system. The article analyses the challenges facing Islamic education in the digital era, such as uncontrolled information penetration and the influence of global culture that can erode local values. On the other hand, it also explores the opportunities offered by digital technology in expanding the reach of Islamic education, such as e-learning, educational apps, and social media that can be used for dawah and interactive learning. With a holistic approach, this article aims to provide strategic recommendations to optimise Islamic education in utilising digital technology, so as to create a society that is not only digitally literate but also has strong spiritual intelligence.